2012
DOI: 10.2119/molmed.2012.00296
|View full text |Cite
|
Sign up to set email alerts
|

Aldo-keto Reductase Family 1 Member C3 (AKR1C3) Is a Biomarker and Therapeutic Target for Castration-Resistant Prostate Cancer

Abstract: Current endocrine treatment for advanced prostate cancer does not result in a complete ablation of adrenal androgens. Adrenal androgens can be metabolized by prostate cancer cells, which is one of the mechanisms associated with progression to castration-resistant prostate cancer (CRPC). Aldo-keto reductase family 1 member C3 (AKR1C3) is a steroidogenic enzyme that plays a crucial role in the conversion of adrenal androgen dehydroepiandrosterone (DHEA) into high-affinity ligands for the androgen receptor (testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 36 publications
7
67
1
Order By: Relevance
“…Thus overexpression of AKR1C3 in CPRC would provide a mechanism to divert trace androgens that remain after ADT to potent androgens via these three pathways within the tumor. Studies have shown that AKR1C3 is overexpressed in prostate cancer cell lines 10-16 fold and up to 3-fold in androgen responsive and androgen independent prostate cancer cell xenografts upon androgen deprivation when measured by qRT-PCR, Table 2 [6, 39-43]. By contrast AKR1C3 expression is repressed by androgens e.g.…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Thus overexpression of AKR1C3 in CPRC would provide a mechanism to divert trace androgens that remain after ADT to potent androgens via these three pathways within the tumor. Studies have shown that AKR1C3 is overexpressed in prostate cancer cell lines 10-16 fold and up to 3-fold in androgen responsive and androgen independent prostate cancer cell xenografts upon androgen deprivation when measured by qRT-PCR, Table 2 [6, 39-43]. By contrast AKR1C3 expression is repressed by androgens e.g.…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…AKR1C3 was also overexpressed in 11/19 soft-tissue metastasis from mCRPC patients by IHC [44, 46][46] and in bone metastasis by qRT-PCR and IHC [47]. Analysis of several studies suggest that AKR1C3 is upregulated in subset of mCRPC patients where estimates are that it is overexpressed at the RNA and protein level in at least one third of all mCRPC patients [39, 43, 44, 47]. These estimates are likely to be conservative since whether patients had received prior second-line ADT therapy was not reported when measuring transcript levels.…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…AKR1C3 has been reported to be expressed in breast and prostate cancers (Lin et al, 2004), and its functions have been extensively studied in these malignancies. In castrationresistant prostate cancer, increased AKR1C3 expression was reported to contribute to the production of high-affinity ligands for the androgen receptor, promoting prostate cancer progression (Hamid et al, 2012;Dozmorov et al, 2010). AKR1C3 has been also suggested as an androgenic enzyme in androgen receptorabundant breast cancer cases but its predominant function has not been fully elucidated (Suzuki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As AKR1C3 has been recently suggested as a new therapeutic target of castration resistant prostate cancer (Hamid et al, 2012), and development of AKR1C3 inhibitors and clinical studies have been ongoing (Loriot et al, 2014), an understanding of the underlying mechanism may be indispensable in making therapeutic choices. Though it is conceivable that AKR1C3 predominantly acts as an androgenmetabolizing enzyme in prostate cancer, our results indicated the up-regulation of Slug and decrease of chemosensitivity by the activation of 11b-PGF2a-FP receptor pathway, may be an alternate possible mechanism underlying prevention of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…AKR1C3 is overexpressed in cell lines deprived of androgens [27,28], in prostate cancer xenografts in castrate mice [24,25,28] and in CRPC patients [2931]. AKR1C3 is involved in all pathways to T and 5α-dihydrotestosterone (DHT) in the prostate due its 17-ketosteroid reductase activity; it reduces 4-androstene-3,17-dione to T (by the canonical pathway) [32]; it reduces 5α-andros-tane-3,17-dione to DHT (by the alternative pathway) [33]; it reduces androsterone to 5α-androstane-3α,17β-diol (3α-diol) which is then oxidized by 17BHSD6 to DHT (by the backdoor pathway) [3436]; and it reduces DHEA to 5-androstene-3β,17β-diol which is converted by 3HSDB1 to T. AKR1C3 inhibitors would block all pathways to T and DHT within the tumor and could surmount drug resistance to Abi and ENZ (Figure 2).…”
Section: Introductionmentioning
confidence: 99%